Special issue : NextGen materials for 3D printing - An, Jia (2018)
Only a handful of materials are well-established in three-dimensional (3D) printing and well-accepted in industrial manufacturing applications. However, recent advances in 3D printable materials have shown potential for enabling numerous novel applications in the future. This special issue, consisting of 2 reviews and 10 research articles, intends to explore the possible materials that could define next-generation 3D printing.